A study of gene action for yield and quality traits of Basmati rice (Oryza sativa L.) following Hayman's graphical approach - Sharma, Aarti; Jaiswal, Hemant Kumar (ORYZA-An International Journal of Rice, 2021)
The present study was conducted on 36 crosses obtained by carrying out a crossing program in nine Basmati rice genotypes following half-diallel mating design. Following, Hayman's graphical and numerical approach to comprehend the genetic system involved in the inheritance of traits, it was concluded that, out of 18 traits, only two traits viz., 100-grain weight, and aroma fulfilled the adequacy of additive-dominance model indicating absence of epistasis. Further, Vr/Wr graph was plotted and genetic components w ere estimated for these twotraits only. By plotting Vr/Wr graph for 100-grain weight and aroma, partial dominance and over-dominance were observed in the inheritance, respectively. The ratio of KD/Kr implied influence of more of recessive alleles in inheritance of 100-grain weight among parents and dominant alleles for aroma genes among parents. Estimates of genetic components indicated the role of both additive and dominance effect in the inheritance of 100-grain weight and aroma. High heritability in narrow sense was observed for the traits.